Análisis de contenido de los influencers indígenas en la plataforma TikTok y su impacto en los jóvenes de 18 a 21 años de la carrera de comunicación de la UNACH periodo julio –diciembre 2022 - Brito Brito, Diego Fernando (2024)
ABSTRACT In the present investigation, the purpose is to learn about the content of Ecuadorian indigenous influencers within the TikTok platform and the impact on young people between 18 and 21 years of age of the communication career where it is implied that the participation of culture indigenous project to be visualized in its cultural part within the TikTok platform, making its characteristics known. TikTok has become a communication tool and even tends to make users part of that digital circle. A content analysis matrix was used where three influencers such as Leonardo Sefla, Nathaly Pilamunga and Elizabeth Guaminga were linked with the main objective of an analysis since they proceeded to understand their cultural aspects. The second tool used is the survey, it is a form where the opinions of the 369 students are extracted. Another support is from the two interviews, towards a social media expert and the selected influencer so that they can give their point of view about social networks, the content and the influence that exists in Tiktok content. The results obtained revealed that the content of Ecuadorian indigenous influencers does influence young people through cultural characteristics and also through the creation of quality content and with this it is demonstrated that there is great interaction of content consumption. Keywords: communication, content, indigenous influencers, TikTok, interaction